Collagen Hydrolysate Prepared from Chicken By-Product as a Functional Polymer in Cosmetic Formulation - Prokopová, Aneta; Pavlačková, Jana; Mokrejš, Pavel; Gál, Robert (Molecules (Basel, Switzerland), 2021)
Chicken stomachs can be processed into collagen hydrolysate usable in cosmetic products. The aim of the study was to verify the effects of a carbopol gel formulation enriched with 1.0% (w/w) chicken hydrolysate on the properties of the skin in the periorbital area after regular application twice a day for eight weeks in volunteers ageed 50 ± 9 years. Skin hydration, transepidermal water loss (TEWL), skin elasticity and skin relief were evaluated. Overall, skin hydration increased by 11.82% and 9.45%, TEWL decreased by 25.70% and 17.80% (always reported for the right and left area). Generally, there was an increase in skin elasticity, a decrease in skin roughness, as the resonance times decreased by 85%. The average reduction of wrinkles was 35.40% on the right and 41.20% on the left. For all results, it can be seen that the longer the cosmetic gel formulation is applied, the better the results. Due to the positive effect on the quality and functionality of the skin, it is possible to apply the cosmetic gel formulation in the periorbital area. The advantage of the product with chicken collagen hydrolysate is also the biocompatibility with the skin and the biodegradability of the formulation.
Keywords: food by-products; cosmetic gel formulation; transepidermal water loss; fyziologie kůže; Chickens; Protein Hydrolysates; elasticity; kůže; proteinové hydrolyzáty; kolagen; zvířata; chicken stomachs; Collagen; hydration; collagen hydrolysate; polymery; Polymers; pružnost; kur domácí; Skin Physiological Phenomena; Elasticity; Cosmetics; kosmetické přípravky; roughness; Animals; aging; Skin